DEVELOPMENT OF FLOW INJECTION METHOD FOR ONLINE DETERMINATION OF THIOCYANATE BASED ON OXIDATION BY PERMANGANATE - Hermin Sulistyarti; Spas D. Kolev; Stephanie Lim (Indonesian Journal of Chemistry, 2010)
The importance of developing method for thiocyanate becomes obvious, because thiocyanate can inhibit iodine uptake of thyroid gland leading to mumps disease. In this work, thiocyanate is oxidized by permanganate in the acid donor stream to cyanide, which is directly converted to hydrogen cyanide. Then, hydrogen cyanide diffuses through a Teflon membrane into acceptor stream containing nickel(II) in ammoniacal buffer to form tetracyanonickelate(II) which is detected spectrophotometrically at 267 nm. Analytical figures of merit were linear up to 50 mg L-1 for thiocyanate, with RSD of 1.34%, and detection limit of 0.07 mg L-1, respectively. Interfering anions were eliminated under stoichiometric amount of permanganate and sample throughput was 20 h-1. The method was validated for determining thiocyanate samples from synthetic and gold process waters with satisfactory results.